Renal and salt gland function in the Jackass penguin (Speniscus [i.e. Spheniscus] demersus Linn.) with special reference to the renal portal system - Oelofsen, B. W.(Burger Wilhelm) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1973.